2008
DOI: 10.1021/ol801397v
|View full text |Cite
|
Sign up to set email alerts
|

Consecutive Cyclization of Allylaminoalkene by Intramolecular Aminolithiation−Carbolithiation

Abstract: Consecutive cyclization of allylaminoalkenes by tandem aminolithiation-carbolithiation proceeded smoothly by using a lithium amide as a lithiating agent as well as protonating agent to give bicyclic amines, octahydroindolizine and hexahydro-1 H-pyrrolizine, in reasonably high yield and diastereoselectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 66 publications
0
19
0
Order By: Relevance
“…In a similar manner, a tandem aminolithiation/carbolithiation reaction allowed the efficient preparation of bicyclic octahydroindolizines and hexahydro-1H-pyrrolizines. When allylaminoalkene 76 was treated with n-BuLi in the presence of a bulky tert-butyltritylamine, the heterocycle 77 was isolated in 85% yield in high diastereomeric ratio (Scheme 11.21) [48]. The authors rationalized the stereochemical outcome of this reaction via the models previously proposed for the carbolithiation step [34,44,48].…”
Section: Intramolecular Carbolithiation Of Alkenesmentioning
confidence: 87%
“…In a similar manner, a tandem aminolithiation/carbolithiation reaction allowed the efficient preparation of bicyclic octahydroindolizines and hexahydro-1H-pyrrolizines. When allylaminoalkene 76 was treated with n-BuLi in the presence of a bulky tert-butyltritylamine, the heterocycle 77 was isolated in 85% yield in high diastereomeric ratio (Scheme 11.21) [48]. The authors rationalized the stereochemical outcome of this reaction via the models previously proposed for the carbolithiation step [34,44,48].…”
Section: Intramolecular Carbolithiation Of Alkenesmentioning
confidence: 87%
“…All attempts to force the cyclization in this case by changing different reaction parameters did not lead to the desired products of intramolecular carbocyclization. It has been demonstrated that a sequential aminolithiation/carbolithiation reaction opens up an efficient route to bicyclic octahydroindolizines and hexahydro-1H-pyrrolizines [49]. When the allylaminoalkene 180 was treated with n-BuLi in the presence of a bulky tert-butyltritylamine, the heterocycle 181 was isolated in 85% yield (Scheme 10.59).…”
Section: N Phmentioning
confidence: 99%
“…The nature of the amine was rationalized by considering the reactivity of the plausible intermediate 183 toward protonation with the corresponding amine. The authors came to the conclusion that carbolithiation of 183 and protonation of less sterically hindered 184 with a bulky amine leads to the desired product of carbocyclization, while protonation of 182 with a less bulky amine leads to the side product [49]. Under the optimized conditions, product 181 was isolated as a 30 : 1 : 0 mixture of diastereomers, and the major diastereomer was determined to be trans,cis-181 by nOe experiments.…”
Section: N Phmentioning
confidence: 99%
See 2 more Smart Citations